EVALUASI KEBIJAKAN SISTEM KEAMANAN BERBASIS TEKNOLOGI KAMERA PENGAMAN DI KOTA BATAM - Achyar Hanif Siregar; Didik Syahputra; Gevrazi Gevrazi; Dika Aditya Putra; Baskoro Wicaksono (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2017)
Batam is a very rapid business climate growth city in Indonesia. In effort strengthen it, has formed a security system policy based security camera technology with intention of creating Batam City as a smart city security field in the Asia Pacific region. It policy is Batam City Local Regulation Number 2 Of 2007 On Security System Throught Security Camera In Vital Objects, Public Facilities, And Spesific Areas In Batam City. Various problems has encountered in last 10 years including the not ideal security cameras quantity, bad security cameras quality, and Security Coordinating Board not implemented. From that, this research purpose is to analyze policy evaluation. Policy evaluation theory used as activity that concerns policy assessment including substance, implementation, and impact. Research method used phenomenology descriptive qualitative approach including primary and secondary data collection techniques, data processing and analysis, and conclusion. Through this research has found results in evaluation form from are first, substance assessment need to forward. Second implementation assessment need to be continue with an improvement. And third, impact assessment need to be continue with an improvement too. Keywords: policy evaluation, security system